2019
DOI: 10.1007/s11302-019-09659-0
|View full text |Cite
|
Sign up to set email alerts
|

P2X3 receptors contribute to muscle pain induced by static contraction by a mechanism dependent on neutrophil migration

Abstract: P2X3 receptors are involved with several pain conditions. Muscle pain induced by static contraction has an important socioeconomic impact. Here, we evaluated the involvement of P2X3 receptors on mechanical muscle hyperalgesia and neutrophil migration induced by static contraction in rats. Also, we evaluated whether static contraction would be able to increase muscle levels of TNF-α and IL-1β. Male Wistar rats were pretreated with the selective P2X3 receptor antagonist, A-317491, by intramuscular or intrathecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 79 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…Elevated neurotransmitter release and peptide co-release with ATP are thought to cause peripheral and central sensitization [ 51 , 58 ]. Because P2X3R is sensitive to nanomolar ATP concentrations, purinergic signal transduction can be adjusted using varying ATP concentrations [ 59 ]. ATP modulates pain sensitivity via changes in sensory neuron voltage-gated ion channels activity, including CaV and NaV [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated neurotransmitter release and peptide co-release with ATP are thought to cause peripheral and central sensitization [ 51 , 58 ]. Because P2X3R is sensitive to nanomolar ATP concentrations, purinergic signal transduction can be adjusted using varying ATP concentrations [ 59 ]. ATP modulates pain sensitivity via changes in sensory neuron voltage-gated ion channels activity, including CaV and NaV [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that P2X3 receptors expressed on gastrocnemius muscle and spinal cord dorsal horn seem to be essential to the development of the acute mechanical muscle hyperalgesia induced by static contraction of the gastrocnemius muscle [26]. It is important to point out that the long-term static contraction produces musculoskeletal pain by similar mechanisms to carrageenan, such as final inflammatory mediators and neutrophil migration [14,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of chronic muscle pain seems to involve more lasting modifications, such as modulation of nociceptive afferent fibers by kinase activation cascade and/or in the expression of some receptors in the nociceptive fibers [11][12][13]. It is interesting to point out that P2X3 receptor, one of the most important receptors related to transmission and modulation of nociceptive signals (Oliveira-Fusaro et al 2017;Teixeira et al 2016), including the nociceptive muscle tissue signaling [14,15], has an involvement with the PKC signaling pathway [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important transducer of nociceptive stimuli, purinergic receptor P2X ligand-gated ion channel 3 (P2 × 3) is a trimeric cation channel that is gated by extracellular ATP and predominantly localized in small-to medium-sized neurons of the DRG [49] and acts as an attractive potential therapeutic target [50]. P2 × 3 can be involved in different pain conditions [51]. Its activation contributes to acute nociceptive behavior, hyperalgesia, and allodynia [52][53][54].…”
Section: Introductionmentioning
confidence: 99%